Effect of Plasma Treatment on Metal Oxide p–n Thin Film Diodes Fabricated at Room Temperature. Issue 10 (1st April 2021) - Khong, Yin Jou; Niang, Kham Man; Han, Sanggil; Coburn, Nigel J.; Wyatt‐Moon, Gwenhivir; Flewitt, Andrew J.
Abstract: There is a need for a good quality thin film diode using a metal oxide p–n heterojunction as it is an essential component for the realization of flexible large‐area electronics. However, metal oxide‐based diodes normally show poor rectification characteristics whose origin is still poorly understood; this is holding back their use in various applications. A systematic study of the origins of the poor performance is performed based on bias‐stress measurements using a cuprous oxide (Cu2 O)/amorphous zinc‐tin oxide (a‐ZTO) heterojunction as an example. This suggests that multiple carrier trapping and thermal release of carriers in defect states stemming from oxygen vacancies at the heterojunction interface is the primary cause of poor rectification. It is demonstrated that a plasma treatment is an effective way to optimize the population of oxygen vacancies at the heterojunction interface based on extensive material analyses, allowing a significant improvement in the diode performance with a much‐enhanced rectification ratio from ≈20 to 10 000, and a consequent facilitation of the next‐generation of ubiquitous electronics. Abstract : Thin film heterojunction diodes fabricated using cuprous oxide and amorphous zinc‐tin oxide at room temperature are rectifying well. The performance of the diodes is hugely improved by oxygen plasma treatment at the interface of the two films. It is suggested that the trap states near the interface are caused by oxygen vacancies and weakly‐bonded oxygen atoms.